Towards the Implementation of MALL: Saudi EFL Instructors’ Attitudes on its Challenges and Integration in EFL Classes - Khan, Raja Muhammad Ishtiaq; Noor Raha, Mohd Radzuan; Shahbaz, Muhammad; Ainol Haryati, Ibrahim (2018)
The integration of computer-assisted language learning (CALL) has delivered great openings for language instructors to develop their usage of technology and implement learner focused learning in teaching practice. Consequently, with the increasing usage of technology in language learning, instructors would have a key role in formulating, arranging and motivating learners to integrate readily available technologies for the development of their language learning. The focus of preset investigation is to explore the attitudes of Saudi English as foreign language (EFL) instructors in the direction of implementing mobile assisted language learning (MALL). The targeted population of the study is Saudi EFL instructors who are currently teaching English in Saudi Arabia. The instruments of the study were mainly a questionnaire and in depth- interview were also conducted to explore the attitudes of EFL instructors. The results of the survey questionnaire and interview depicted moderately positive attitudes of the participants in using mobile phones for language learning and teaching activities. The findings also suggested that the existence of some perceived challenges might be a great hurdle for mobile phones integration in EFL learning and teaching in Saudi Arabia. Most of the instructors reported that they do not use mobile phones or MALL activities in their EFL classes. Results exhibited that the EFL teachers did not have the required skills to use/develop MALL activities. The study also offers recommendations and suggestions on how to implement MALL and remove potential barriers to MALL implementation in EFL contexts.